Modelling time performance for construction of public building projects in peninsular Malaysia / Hasli Ibrahim - Ibrahim, Hasli (Institute of Graduate Studies, UiTM, 2012)
Completing project on time is symbolic of an efficient construction project. However, project delay is a common issue in construction industry today. The failure in estimating reasonable construction duration will jeopardize the successful completion of the projects. There are needs to establish a tool in order to estimate construction time performance. Thus, this study focuses on developing a model to predict reasonable construction duration in order to improve construction time performance for public building projects in Peninsular Malaysia. This study cover four types of public sector building projects namely; school and education building; public building; health and medical building; and security building.